Characterization of H1N2 variant influenza viruses in pigs - Duff, Michael Alan (Kansas State University, 2014)
With introduction of the 2009 pandemic H1N1 virus (pH1N1) into swine herds, reassortment between the pH1N1 and endemic swine influenza viruses (SIVs) has been reported worldwide. Recently, reassortant H3N2 and H1N2 variant SIVs that contain the M gene from pH1N1 virus and the remaining seven genes from North American triple-reassortant (TR) SIVs have emerged. These variant viruses have caused more than 300 cases of human infections and one death in the USA, creating a major public health concern. To date, the pathogenicity and transmissibility of H1N2 variant viruses in pigs has not been investigated. Through passive surveillance, we have isolated two genotypes of reassortant H1N2 viruses with pH1N1 genes from diseased pigs in Kansas. Full genome sequence and phylogenetic analysis showed that one is a swine H1N2 variant virus (swH1N2v) with the M gene from pH1N1; the other is a reassortant H1N2 virus (2+6 rH1N2) with six internal genes from pH1N1 and the two surface genes from endemic North American TR H1N2 SIVs. Furthermore, we determined the pathogenicity and transmissibility of the swH1N2v, a human H1N2 variant (huH1N2v), and the 2+6 rH1N2 in pigs using an endemic TR H1N2 SIV (eH1N2) isolated in 2011 as a control. All four viruses were able to infect pigs and replicate in the lungs. Both H1N2 variant viruses caused more severe lung lesions in infected pigs when compared to the eH1N2 and 2+6 rH1N2 viruses. Although all four viruses are transmissible in pigs and were detected in the lungs of contact animals, the swH1N2v shed more efficiently than the other three viruses in the respective sentinel animals. The huH1N2v displayed delayed and inefficient nasal shedding in sentinel animals. Taken together, the human and swine H1N2 variant viruses are more pathogenic and the swH1N2v more transmissible in pigs and could pose a threat to public and animal health.
Keywords: Influenza A virus; 2009 influenza A H1N1 pandemic; Reassortment; Swine influenza A virus; H1N2 variant; Influenza A virus in pigs; Animal Diseases (0476); Microbiology (0410); Virology (0720)